Fibrodysplasia Ossificans Progressiva: What Have We Achieved and Where Are We Now? Follow-up to the 2015 Lorentz Workshop - de Ruiter, Ruben D.; Smilde, Bernard J.; Pals, Gerard; Bravenboer, Nathalie; Knaus, Petra; Schoenmaker, Ton; Botman, Esmée; Sánchez-Duffhues, Gonzalo; Pacifici, Maurizio; Pignolo, Robert J.; Shore, Eileen M.; van Egmond, Marjolein; et al. (Frontiers in Endocrinology, 2021)
Fibrodysplasia ossificans progressiva (FOP) is a ultra-rare progressive genetic disease effecting one in a million individuals. During their life, patients with FOP progressively develop bone in the soft tissues resulting in an increasing immobility and early death. A mutation in the ACVR1 gene was identified as the causative mutation of FOP in 2006. After this, the pathophysiology of FOP has been further elucidated through the efforts of research groups worldwide. In 2015, a workshop was held to gather these groups and discuss the new challenges in FOP research. Here we present an overview and update on these topics,